The decomposition of sociology - Horowitz, Irving Louis 1929-2012 (Oxford Univ. Press, 1993)
The author examines the field of sociology and the closing of many sociology departments and then proposes "an alternative, plsitive view of social research."--Jacket.
Keywords: Sociologie - États-Unis - Histoire; Sociologie - Étude et enseignement - États-Unis; Sociologie; Geschichte; Soziologie; Sociology -- Study and teaching -- United States; Sociology -- United States -- History; USA